Expression of ezrin radixin moesin proteins in the adult subventricular zone and the rostral migratory stream - Persson, Å.; Lindwall, C.; Curtis, M.A.; Kuhn, H.G. (Neuroscience, 2010)
Continuous proliferation occurs in the adult subventricular zone (SVZ) of the lateral ventricles throughout life. In the SVZ, progenitor cells differentiate into neuroblasts, which migrate tangentially along the rostral migratory stream (RMS) to reach their final destination in the olfactory bulb. These progenitor cells mature and integrate into the existing neural network of the olfactory bulb. Long distance migration of neuroblasts in the RMS requires a highly dynamic cytoskeleton with the ability to respond to surrounding stimuli. Radixin is a member of the ERM (Ezrin, Radixin, Moesin) family, which connect the actin cytoskeleton to the extracellular matrix through transmembrane proteins. The membrane-cytoskeleton linker proteins of the ERM family may regulate cellular events with a high demand on cytoskeleton plasticity, such as cell motility. Recently, specific expression of the ERM protein ezrin was shown in the RMS. Radixin however has not been characterized in this region. Here we used immunohistochemistry and confocal microscopy to examine the expression of radixin in the different cell types of the adult subventricular zone niche and in the RMS. Our findings indicate that radixin is strongly expressed in neuroblasts of the adult RMS and subventricular zone, and also in Olig2-positive cells. We also demonstrate the presence of radixin in the cerebral cortex, striatum, cerebellum, thalamus, hippocampus as well as the granular and periglomerular layers of the olfactory bulb. Our studies also reveal the localization of radixin in neurosphere culture studies and we reveal the specificity of our labeling using Western blotting. The expression pattern demonstrated here suggests a role for radixin in neuronal migration and differentiation in the adult RMS. Understanding how adult neuronal migration is regulated is of importance for the development of new therapeutic interventions using endogenous repair for neurodegenerative diseases.